Mambadakan Paja: Pergumulan Islam dan Tradisi Lokal di Nagari Kamang Mudiak Kabupaten Agam Sumatera Barat - Gusnanda Gusnanda; Novizal Wendry; Luqmanul Hakim (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
A child's birth in Islamic teachings will be welcomed with akikah, but the archipelago people have local traditions in welcoming this event. The dialectic between religious teachings and local traditions gave birth to new traditions: assimilation or acculturation of Islamic teachings and community traditions. The tradition of holding Paja in Nagari Kamang Mudiak, Agam Regency, West Sumatra, is one of the traditions born from the Islamic dialectic process and the Minangkabau's local culture people. This research aims to describe the tradition of carrying out Paja due to the dialectic of akikah teaching in Islam as a guide to the Prophet's Sunnah in the socio-cultural context of the society in the Religion District of West Sumatra. This research is qualitative research using a phenomenological approach and cultural interpretation. This research found that society tries to articulate Islamic teachings about akikah sunna contextually. The old and young dialectic influences the implementation of this tradition in its development in Minangkabau. This dialectic patterned its implementation into two models, namely traditionalist and modernist. The tradition of making the Paja continues with both models. As for the motive for the implementation of this tradition is for theological and cultural reasons.